Bicarotid Trunk in the Domestic Cat. (22nd September 2015) - More, S.; Watson, A.; Stein, L. E.
Summary: The origin of the pair of common carotid arteries in the cat is inadequately described, and there are conflicting accounts in English veterinary anatomy textbooks published in the USA. We found one‐quarter of 40 adult domestic cats dissected had a bicarotid trunk (5 female, 5 male). When present, the bicarotid trunk arose from the brachiocephalic trunk approximately midway between the expected origins of the more frequently independently arising left and right common carotid arteries, and on average, it was 5.6 mm in length. Our findings make the incidence, topographical and measurement information available so that students and veterinarians can be aware of this not insignificant variation in branching of the major arteries, forming a bicarotid trunk, in the cranial mediastinum of domestic cats.